The expression 'Public Law' annulment in the Chilean Law - Agüero San Juan, Claudio (EUNOMÍA. Revista en Cultura de la Legalidad, 2017)
This paper aims to make a brief presentation of the meaning of the expression 'Public Law annulment'. The paper argues that this locution designates an idiosyncratic dogmatic and jurisprudential argument in the Chilean Administrative Law. The paper describes his trajectory and distinguishes among four dogmatic versions of it. It then analyzes how an analysis of the trajectory of a dogmatic argument contributes to the realistic theory of law.doi: https://doi.org/10.20318/eunomia.2017.3654
Keywords: public law annulment; administrative extralegal lawmaking; dogmatic argument